Succeeding with difficult clients : applications of cognitive appraisal therapy - Wessler, Richard L. (Practical resources for the mental health professional., 2001)
"I know that I am doing therapy correctly and well, so why aren't some of my clients changing?" "Why do I feel anxious when I think about my next session with that difficult client?" When psychotherapy stalls, it's time to try new ideas. The authors' experience with difficult clients -- uncooperative, hostile, uncommitted to change -- gave them a new perspective on working with therapeutic impasses. Papers describing Cognitive Appraisal Therapy have appeared in many books and journals, and now for the first time these ideas are compiled into a single volume. Heavily influenced by the psychothe